The Effect of The Application of CPS and PBL Models on Students' Mathematical Creative Thinking Abilities in Junior High School - Allyana Dwi Reza; Nizlel Huda; Khairul Anwar (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
This study aims to determine whether there are differences in the results of the influence of the application of the Creative Problem Solving (CPS) model, the Problem Based Learning (PBL) model and the Direct Instruction (DI) model in improving mathematical creative thinking skills in the material of quadrilaterals and triangles of class VII students of SMPN 9 Kota Jambi. Using an experimental posttest only control research design, this study involved the population of all class VII students of SMPN 9 Kota Jambi in the 2023/2024 academic year totaling 204 students from 7 classes. Through the Random Sampling technique , three classes were selected as samples, namely VII A, VII B, and VII C. Data collection was carried out using two instruments: observation sheets for the implementation of learning and evaluation tests for mathematical creative thinking skills. To analyze the collected data, statistical analysis using One way Anova showed a significance value of 0.000 which was smaller than 0.005. These findings indicate different effects of the application of the three learning models - CPS, PBL, and DI - on improving mathematical creative thinking skills. Posttest data showed that the group of students who received learning with the CPS model achieved an average score of 16.94, while the PBL group obtained an average of 16.26. Both groups showed superior results compared to the group using the DI (Direct Instruction) learning model